LIBRARY SERVICES FROM HOME (LSFH) - Rian Dwi Hapsari; Kuncoro G. Pambayun; Heri Iman Santoso (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: The author focuses on limited online library services, direct verbal communication, access to referrals, librarian resource conditions and diversity of LSFH support facilities. Purpose: This study aims to know the LSFH policy by the Library in deciding the spread of COVID-19 on IPDN Method: This study uses qualitative methods. The technique of collecting data observation, documentation, and online interviews of 10 respondents consisting of 5 LSFH librarians and 5 LSFH service recipients Result: The results showed that the e-Resources Service was the easiest to implement and improved. Scientific Publication Services had the greatest technical challenges due to constrained server and application access, while the Library Guidance Service was a challenge to the capability and quality of delivering a librarian Conclusion: The LSFH policy by IPDN Library runs quite well. The writer's suggestion to equalization of the capacity of librarians with sufficient bandwidth, librarians' capacity improvement, and improvement of applications and scientific publication server.